Evaporation of communitarian ethics from public life in India: Some exploratory hypotheses - Kabra, Kamal Nayan (1995)
"Drawing brief supportive evidence from findings of the recent Vohra Committee, the author presents a detailed analytical account of various factors causing prevalence of unethicality in our contemporary public life emerging mainly from politicians (including political parties) businessmen-crime nexus. He also discusses, in this regard, the contribution of the defective model of our economic development. He concludes emphasising the need to maintain bonds of social and communitarian values with institutions, organisations and behaviour patterns"
Keywords: Civil service - India; Public administration - India; Political philosophy - India; Political philosophy